Legislative Regulation of Labor Relations of Professional Athletes and Coaches in Russia: History and Present State - G. A. Popov (Теоретическая и прикладная юриспруденция)
The article examines the history of the formation of legislative regulation of labor relations of “special subjects” of labor law of the Russian Federation — professional athletes and coaches (sports subjects), as well as the current state of legal regulation of these relations. The author comes to the conclusion that the regulatory and legal regulation of the labor activity of sports subjects in Russia has a short history, equal to about three decades: until the end of the 80s of the XX century, professional sports were not given due attention by the state, and the relations that existed in this area were not properly regulated, which hindered the development of professional sports and created threats to the violation of the rights and legitimate interests of athletes and coaches. After the collapse of the USSR, the regulatory regulation of labor relations of sports subjects went through several stages, each of which had an invaluable impact on the development of professional sports in the Russian Federation. As a result of “trial and error”, a fairly extensive regulatory framework was created, which made it possible to achieve stability and legality in regulating the work of professional athletes and coaches. However, a number of legal conﬂicts and gaps that need to be addressed still remain.